Treatment of Patients with Hypertension Induced by Covid 19 - Tashtemirova I.M (Genius Journals, 2023)
The truth that e infection employments angiotensin-converting protein 2 as a receptor for entering the target cell, and the tall predominance of hypertension and other cardiovascular illnesses among patients with COVID-19, have caused genuine dialogs on the administration of such patients. This agreement of specialists from the Uzbek Restorative Society for Blood vessel Hypertension analyzed the existing information on the relationship between COVID-19 and hypertension, the pathophysiological angles of the entrance of the infection into target cells and the utilize of renin-angiotensin-aldosterone framework inhibitors in patients with hypertension and COVID-19.
Keywords: COVID-19; coronavirus; angiotensin converting enzyme